3(x-1)=9x-3(2x+1)

Simple and best practice solution for 3(x-1)=9x-3(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)=9x-3(2x+1) equation:


Simplifying
3(x + -1) = 9x + -3(2x + 1)

Reorder the terms:
3(-1 + x) = 9x + -3(2x + 1)
(-1 * 3 + x * 3) = 9x + -3(2x + 1)
(-3 + 3x) = 9x + -3(2x + 1)

Reorder the terms:
-3 + 3x = 9x + -3(1 + 2x)
-3 + 3x = 9x + (1 * -3 + 2x * -3)
-3 + 3x = 9x + (-3 + -6x)

Reorder the terms:
-3 + 3x = -3 + 9x + -6x

Combine like terms: 9x + -6x = 3x
-3 + 3x = -3 + 3x

Add '3' to each side of the equation.
-3 + 3 + 3x = -3 + 3 + 3x

Combine like terms: -3 + 3 = 0
0 + 3x = -3 + 3 + 3x
3x = -3 + 3 + 3x

Combine like terms: -3 + 3 = 0
3x = 0 + 3x
3x = 3x

Add '-3x' to each side of the equation.
3x + -3x = 3x + -3x

Combine like terms: 3x + -3x = 0
0 = 3x + -3x

Combine like terms: 3x + -3x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3y^3-22y^2+7y=0 | | Ln(x-1)+ln(5x)=3 | | X-35=7(2x-5)-13x | | x-35=x-35 | | x-7x=-7-6 | | 6-2[-4(2-7)-3(2-3)]= | | (x-4)(4x+5)=0 | | 121x^2-25=0 | | 2x+6=4x+6 | | 3x^2+8x+3=0 | | 3-7[7-(9y-4)]= | | 6x+5y=110000 | | 7=-4t | | 7(5y-4)+2(4y+6)= | | 7(5y-6)+2(4y+6)= | | 2-14=-8t+4t | | 5x^2+11x-66=0 | | 5(y*2-4)=-21y | | 6x^2+x=2 | | 6t*2=7 | | s*2-9=0 | | 4(6x-9)=3(12x-8) | | 6z-5=7z-7 | | 6(y+1)-5=7 | | 7-z=3+z+4-2z | | 2u=u-6 | | 8x-4=(2x+1) | | 2x^2+3y^2-30=0 | | 2w+3=7w+13 | | 4y^2+11y+7=5 | | 5y-8=3y+5 | | 4x-3x-7=6x |

Equations solver categories